Fig. 3 in Dipnoan from the Upper Triassic of East Greenland and remarks about palaeobiogeography of Ptychoceratodus - Pawlak, Wojciech; Tałanda, Mateusz; Sulej, Tomasz; Niedźwiedzki, Grzegorz (Zenodo, 2020)
Fig. 3. Principal Component Analysis of species of Ptychoceratodus dental plates. A. Lower dental plates. B. Upper tooth plates. In the analysis we used α, δ1, δ2, δ3, BCp, C1C2, and C1Cp measurements sensu Vorobyeva and Minikh (1968). White rectangles mean specimens from Macknight Bjerg locality (East Greenland) described herein. Published as part of Pawlak, Wojciech, Tałanda, Mateusz, Sulej, Tomasz & Niedźwiedzki, Grzegorz, 2020, Dipnoan from the Upper Triassic of East Greenland and remarks about palaeobiogeography of Ptychoceratodus, pp. 561-574 in Acta Palaeontologica Polonica 65 (3) on page 565, DOI:10.4202/app.00679.2019, http://zenodo.org/record/12195358